1984
DOI: 10.1007/bf01410258
|View full text |Cite
|
Sign up to set email alerts
|

Frequency dependent linear viscoelastic properties of ordered polystyrene latices

Abstract: An experimental investigation of linear rheological properties of monodisperse ordered latex dispersions has been carried out. Measurements of the dynamic shear modulus and the dynamic viscosity in the frequency range between 0.04 Hz and 2500 Hz are reported. The volume fraction and the electrolyte concentration were variables in the experiment. The results show that a description of the rheological behaviour with a simple linear phenomenological equation is not possible. The measured dynamic moduli can only b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1987
1987
2000
2000

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The linear viscoelastic behaviour of a system which is purely viscous for co --* 0 and viscoelastic for co --+ oo [6] figure 1 the results are shown together with the theoretical predictions. The first conclusion which can be drawn is that more than one relaxation time is present (as expected); this is evident from the asymmetry of t/" as a function of co. Further it is observed that the measurements for a = 2 8 n m and a = 76nm roughly coincide.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…The linear viscoelastic behaviour of a system which is purely viscous for co --* 0 and viscoelastic for co --+ oo [6] figure 1 the results are shown together with the theoretical predictions. The first conclusion which can be drawn is that more than one relaxation time is present (as expected); this is evident from the asymmetry of t/" as a function of co. Further it is observed that the measurements for a = 2 8 n m and a = 76nm roughly coincide.…”
Section: Resultsmentioning
confidence: 83%
“…For reasons of simplicity the calculations involve only the two-body distribution function which at equilibrium (superscript 0) is related to the radial distribution function g (r) by p0 (xi, x2) = n 2 g (r) (6) where n is the number density and r = ]x 1 -x2].…”
Section: ) J=lmentioning
confidence: 99%
See 1 more Smart Citation
“…The radial distribution function g(r ) appearing in Eq. [7] depends on the surface potential of the particles, which greatly complicates a rigorous inversion of Eq. [7] to obtain the pair potential from G ∞ measurements.…”
Section: Extracting Colloidal Surface Chargementioning
confidence: 99%
“…The relationship between the high-frequency modulus and the interaction potential is deduced from the well-known Zwanzig and Mountain formula [7] neglecting hydrodynamic interactions (51),…”
Section: Extracting Colloidal Surface Chargementioning
confidence: 99%